Portuguese as a Host Language for Venezuelans: teaching strategies and pratices in times of pandemics - Sene, Lígia Soares; Matos, Tainara Lucia Corrêa de; Gileno, Rosângela Sanches da Silveira (Universidade Estadual Paulista, 2021)
Due to the COVID-19 health crisis that afflicted the world in early 2020, language teaching and learning courses in Brazil have (re)created teaching strategies for online offer. In this text, we present the teaching-learning strategies developed, in 2020, by the project Portuguese as a Host Language for Venezuelans, offered by the Center for Languages and Teacher Development of the Faculty of Sciences and Letters of Unesp in Araraquara. The project aimed to offer, free of charge, emergency and remote teaching of Portuguese, Brazilian variant, to Venezuelan students, both for adults and children, who were living in the interior of São Paulo. This text is divided into three parts: in the first, we bring the trajectory of classroom teaching to online; in the second, we describe the teaching strategies and present the profile of the students; and in the third, the assessment they made about the teaching strategies.